Quantifying Nonnative Interactions in the Protein-Folding Free-Energy Landscape - Mouro, Paulo Ricardo [UNESP]; Contessoto, Vinicius de Godoi [UNESP]; Chahine, Jorge [UNESP]; Oliveira, Ronaldo Junio de; Pereira Leite, Vitor Barbanti [UNESP] (Cell Press, 2016)
Protein folding is a central problem in biological physics. Energetic roughness is an important aspect that controls protein-folding stability and kinetics. The roughness is associated with conflicting interactions in the protein and is also known as frustration. Recent studies indicate that an addition of a small amount of energetic frustration may enhance folding speed for certain proteins. In this study, we have investigated the conditions under which frustration increases the folding rate. We used a C-alpha structure-based model to simulate a group of proteins. We found that the free-energy barrier at the transition state (Delta F) correlates with nonnative-contact variation (Delta A), and the simulated proteins are clustered according to their fold motifs. These findings are corroborated by the Clementi-Plotkin analytical model. As a consequence, the optimum frustration regime for protein folding can be predicted analytically.